TRADISI GAWAI DAYAK DALAM KAITANNYA DENGAN NILAI-NILAI DALAM QUERIDA AMAZONIA - Ari, Thoras; Tinenti, Hemma Gregorius (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
This research began with the author's concern about the increasing erosion of values in the Dayak Gawai tradition. Gawai is only seen as a festival event that only contains fun. This causes a shift in meaning as a form of expression of gratitude and building an attitude of solidarity. This research study is a cultural study in relation to Pope Francis' Apostolic Exhortation in the Querida Amazonia Document. The method used in the research is a qualitative method, the technique used to obtain data is interviews. The results of the interview were then linked to points related to Querida Amzonia's values. The research results show that there is no conflict between culture and the Catholic faith. The author realizes that this paper has many shortcomings, for example the data mining method which only uses three informants and the rigid analysis technique of interview results. So the next suggestion for the author is to increase the number of informants and look at the application of gadgets to several Dayak ethnic groups as a comparison.